Analisis Penerimaan Pengguna Sistem Informasi Hibah dan Bantuan Sosial Dengan Technology Acceptance Model: User Acceptance in Social Grant System Using Technology Acceptance Model - VELISYA UMBOH; Dirko G.S Ruindungan; Sary D.E Paturusi (Jurnal Teknik Informatika, 2024)
Abstract — The North Bolaang Mongondow Regency Government through Community Welfare (Kesra) has currently launched the Grant and Social Assistence Information System (SIABAS). This information system is intended to make it easier for applicants who will submit files for grant assistance and social assistance. The purpose of this study is to determine the status of user acceptance of the Grant and Social Assistance Information System (SIABAS). This research uses quantitative methods with the Thechnology Acceptance Model (TAM) model.  The sample in this study contained 100 respondents and data processing using the PLS-SEM method with the help of the SmartPLS application version 4.0. The result of this study is perceived usefulness affects the receipt of Information System Grants and Social Assistance. Of the three hypotheses proposed, one hypothesis was rejected, namely the relationship of perceived ease of use with acceptance of IT because the t-test value was 1.117. This research resulted in recommendations to the application development team to focus more on the services provided to application users to enable users to use the application. Keywords: Grant and Social Assistance Information System; Partial Least Squares Structural Equation Modeling; SmartPLS; Technology Acceptance Model; User Acceptance   Abstrak — Pemerintah Kabupaten Bolaang Mongondow Utara melalui Kesejahteraan Masyarakat (Kesra) saat ini telah meluncurkan Sistem Informasi Hibah dan Bantuan Sosial (SIABAS). Sistem informasi ini dimaksudkan untuk mempermudah pemohon yang akan memasukkan berkas bantuan hibah dan bantuan sosial. Tujuan dari penelitian ini adalah untuk mengetahui status penerimaan pengguna terhadap Sistem Informasi Hibah dan Bantuan Sosial (SIABAS). Penelitian ini menggunakan metode kuantitatif dengan model Technology Acceptance Model (TAM). Sampel pada penelitian ini terdapat 100 responden dan pengolahan data menggunakan metode PLS-SEM dengan bantuan aplikasi SmartPLS versi 4.0. Hasil penelitian ini adalah perceived usefulness mempengaruhi penerimaan Sistem Informasi Hibah dan Bantuan Sosial. Dari tiga hipotesis yang diajukan, terdapat satu hipotesis yang ditolak yaitu hubungan perceived ease of use dengan acceptance of IT karena nilai t-test sebesar 1,117. Penelitian ini menghasilkan rekomendasi kepada tim pengembang aplikasi untuk lebih fokus pada pelayanan yang diberikan kepada pengguna aplikasi untuk mempermudah pengguna dalam menggunakan aplikasi. Kata Kunci: Sistem Informasi Hibah dan Bantuan Sosial; Pemodelan Persamaan Struktural Kuadrat Terkecil Parsial; SmartPLS; Model Penerimaan Teknologi; Penerimaan Pengguna